Childhood Wounds, Attachment Styles and Adult Intimacy: A Narrative Review - Adiningsih, Berthy Sri Utami; Rahman, Ainun Najib Febrya (ProNers, 2026)
Background: Early traumatic experiences, including neglect, abandonment, or emotional distress, have repeatedly proven in research to have a major impact on an individual’s attachment behaviours in adulthood. These childhood painful experiences might appear in adult relationships as insecure attachment styles (anxious, avoidant, or disorganized/fearful attachment) and influence how they build intimacy with other people. Method: This narrative review was reported in accordance with the Scale for the Assessment of Narrative Review Articles (SANRA). A structured search of two databases, Google Scholar and ScienceDirect, used the keywords “childhood wound AND attachment styles AND adult intimacy” and “childhood wound AND adult intimacy” for articles published between 2010 and 2025. Records were screened in sequential stages, with additional sources identified from the reference lists of relevant articles; 7 primary studies met the inclusion criteria. Because only two databases were searched, the search was not exhaustive, and no formal risk-of-bias appraisal was undertaken. Results: 7 (seven) included articles originate from Asia, North America, and Oceania, consisting of 6 (six) quantitative articles and 1 (one) qualitative article published in 2010 (n=1), 2014 (n=1), 2019 (n=1), 2020 (n=1), 2023 (n=1), and 2024 (n=2). Three themes were identified through thematic synthesis: (1) psychological issues and the role of health professionals; (2) relationship quality; and (3) impact on the parenting role. Transforming insecure attachment into secure attachment requires routine screening for adverse childhood experiences (ACEs) and attachments, followed by trauma-informed, attachment-informed therapies and self-regulation improvement. Conclusion: Further research on the connection between childhood wounds, attachment styles, and adult non-romantic intimacy needs to be explored more, including the validation and generalisation of interventions recommended from previous studies.